Proximal Foundations of Jealousy: Expectations of Exclusivity in the Infant's First Year of Life. (October 2016) - Hart, Sybil L.
In this synthesis, we summarize studies that yielded evidence of jealousy in young infants. To shed light on this phenomenon, we present evidence that jealousy's foundation rests on history of dyadic interactions with caregivers which engender infants' expectations of exclusivity, and on maturation of sociocognitive capacities that enable infants to evaluate whether an exchange between their caregiver and another child represents a violation of that expectation. We conclude with a call for greater study of the antecedents and sequelae of both normative and atypical presentations of jealousy. In addition, we recommend approaches that address jealousy across a range of relationships, both within and beyond those which include attachment figures.